2022
DOI: 10.3390/plants11131698
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity against Foodborne Pathogens and Inhibitory Effect on Anti-Inflammatory Mediators’ Production of Brazilin-Enriched Extract from Caesalpinia sappan Linn

Abstract: Caesalpinia sappan L. heartwood was collected from Mae Chaem District, Chiang Mai Province, Thailand. Crude extracts were prepared by Soxhlet’s extraction using 50, 60, and 70% of ethanol (EtOH) at 50, 60, and 70 °C, and the brazilin content was measured using reversed-phase high performance liquid chromatography (RP-HPLC). The antibacterial activity against foodborne pathogens and anti-inflammatory aspects were investigated. C. sappan, prepared from 70% EtOH at 70 °C (E70T70), significantly (p < 0.05) exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
9
1
Order By: Relevance
“…These results indicate that C. sappan wood extract can inhibit the growth of E. coli , (MIC: 16–32 mg/ml). The MIC obtained in the present study was lower than that reported in a study that determined the antibacterial activity of C. sappan wood extract against foodborne pathogens, including S. aureus , E. coli , S. enteritidis, and V. parahaemolyticus , with a MIC of 200 mg/ml ( Pattananandecha et al ., 2022 ). But it showed higher than a previous which indicated that ethanolic extracts of C. sappan wood extract can be used against bacteria that cause chronic wound infection, such as S. aureus , with a MIC value of 0.625 mg/ml ( Temrangsee, 2011 ) and MIC/MBC 2/2 mg/ml ( Kawari et al , 2016 ).…”
Section: Discussioncontrasting
confidence: 81%
“…These results indicate that C. sappan wood extract can inhibit the growth of E. coli , (MIC: 16–32 mg/ml). The MIC obtained in the present study was lower than that reported in a study that determined the antibacterial activity of C. sappan wood extract against foodborne pathogens, including S. aureus , E. coli , S. enteritidis, and V. parahaemolyticus , with a MIC of 200 mg/ml ( Pattananandecha et al ., 2022 ). But it showed higher than a previous which indicated that ethanolic extracts of C. sappan wood extract can be used against bacteria that cause chronic wound infection, such as S. aureus , with a MIC value of 0.625 mg/ml ( Temrangsee, 2011 ) and MIC/MBC 2/2 mg/ml ( Kawari et al , 2016 ).…”
Section: Discussioncontrasting
confidence: 81%
“…Furthermore, prominent antibacterial activity was observed for extracts and fractions from C. sappan. Brazilin, one of the major active compounds in C. sappan, has been reported to show noteworthy antibacterial activity against antibiotic-resistant bacteria, including MRSA [27].…”
Section: Resultsmentioning
confidence: 99%
“…These cells have been central to evaluating the efficacy of plant extracts. For instance, an extract of Caesalpinia sappan prepared using 70% ethanol at 70°C demonstrated the ability to inhibit pro-inflammatory mediators, specifically COX-2, in HT-29 cells ( Pattananandecha et al, 2022 ). Additionally, the cytotoxicity of Prangos ferulacea was assessed in terms of its impact on the survival of HT-29 cells, with an IC 50 value determined to be 82.15 ± 0.02 μg/mL ( Jalil Sarghaleh et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%